The Effect of Mg Adding in Recycled Aluminum Casting on Tensile Strength and Microstructure - Syamsul Hadi; Ahmad Hailala Nur Aziz; Pipit Wahyu Nugroho; Muhammad Akhlis Rizza; Hangga Wicaksono (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
The problems faced are aluminium (Al) waste from industries that damage the environment and scarcity of Al raw materials that need to be recycled from used Al. The research objective was to determine the effect of adding magnesium (Mg) to used Al casting on the tensile strength and microstructure and to determine the comparison of the tensile strength of the Al material used by the piston to the brake lining and drum of motorcycles. The research method includes casting Al used pistons, brake lining and drum, testing the tensile strength and microstructure due to the addition of 0.1; 0.2; 0.5 and 1.0% by weight Mg to the tensile strength and microstructure. The results showed that the addition of Mg 0.5% by weight could increase the tensile strength of 92.96% from 71 MPa to 137 MPa for brake lining as the optimum value which further decreased the tensile strength by 19.7% at the addition of 1% Mg to 110 MPa. Drum material also experienced an increase in tensile strength of 33.71% from 89 MPa to 119 MPa as the optimum value where the tensile strength decreased by 5.88% for the addition of 1% Mg to 112 MPa. The two values of the tensile strength of the brake lining and drum components are lower than those of the piston component valued at 147 MPa, and with the addition of Mg, Mg2Si is formed which can reduce the porosity of the microstructure, thereby increasing its strength.